Acute ischemic events after COVID‐19 infection in patients undergoing maintenance hemodialysis. Issue 2 (27th December 2021) - Ozkaya, Etem; Taskent, Ismail; Somay, Rifat; Ocal, Gonca; Heybeli, Cihan
Abstract: Introduction: Patients undergoing maintenance hemodialysis have unique risk factors that render them prone to ischemia. To what extent coronavirus infectious disease 2019 (COVID‐19) increases this risk is unknown. Methods: This retrospective cohort study included incident patients undergoing maintenance hemodialysis from one city in Turkey. A comparison was made between those who developed COVID‐19 and those who did not for clinical variables. Independent predictors of acute ischemic complications in the total cohort were assessed using the logistic regression analysis. Findings: By the start of the pandemic in Turkey, 33 of 154 (21.4%) patients developed COVID‐19. During the 15 months of median follow‐up after the start of the pandemic, 16 (10.4%) patients developed acute ischemic complications. These included acute myocardial infarction (n = 10), acute ischemic stroke (n = 4), acute peripheral artery thrombosis (n = 1), and pulmonary thromboembolism (n = 1). Overall, acute ischemic events occurred more commonly in those who experienced COVID‐19 (24.2% vs. 6.6%, p  = 0.007). Ischemia‐free survival was significantly shorter in the COVID‐19 group ( p  = 0.001). In the eight patients with COVID‐19, ischemic complications emerged at a median 185 (range 21–306) days after the diagnosis of COVID‐19. While age, dialysis vintage, and experience of COVID‐19 were found as factors significantly associated with the development of acute ischemic events in univariate analysis, the association between COVID‐19 and acute ischemia remained significant in the multivariate regression model (odds ratio 3.99, 95% CI [1.3, 12.13], p  = 0.016). During the pandemic, 23 (14.9%) patients died. Overall survival was significantly shorter among those who developed acute ischemic event ( p  < 0.001). The hazard ratio of acute ischemic event for death was 6.76 (95% CI [2.92, 15.66], p  < 0.001). Discussion: A considerable number of patients undergoing maintenance hemodialysis developed acute ischemic complications weeks to months after the resolution of COVID‐19. Hemodialysis patients appear to require specific interventions in order to prevent subsequent acute ischemic events after the resolution of COVID‐19.